2016
DOI: 10.21037/jtd.2016.10.29
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline combination for ventilator-associated pneumonia caused by extensive drug-resistant Acinetobacter baumannii

Abstract: Background: Extensive drug-resistant Acinetobacter baumannii (XDR A. baumannii) has emerged as an important pathogen in patients with ventilator-associated pneumonia (VAP) worldwide. This study determined whether or not combination tigecycline (TGC) treatment improved the short-term outcome of patients with XDR A. baumannii-induced VAP. Methods: Fifty-eight patients admitted to our intensive care unit (ICU) with confirmed XDR A. baumannii VAP between January 2011 and June 2013 were retrospectively studied. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Recent meta-analyses and retrospective studies show that TGC is not associated with higher survival and may even cause more deaths and other serious side effects in severe forms of infectious disease. [ 21 23 ] The FDA in particular, warned against the use of TGC for serious infections in 2010. In contrast, other studies have shown that TGC therapy, when administered as a constituent of combination therapy, (especially high-dose TGC-based therapy), can be effective and can reduce the mortality associated with the severe forms of infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses and retrospective studies show that TGC is not associated with higher survival and may even cause more deaths and other serious side effects in severe forms of infectious disease. [ 21 23 ] The FDA in particular, warned against the use of TGC for serious infections in 2010. In contrast, other studies have shown that TGC therapy, when administered as a constituent of combination therapy, (especially high-dose TGC-based therapy), can be effective and can reduce the mortality associated with the severe forms of infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…In two retrospective studies evaluating tigecycline monotherapy (100 mg IV loading dose, then 50 mg IV q12h) versus tigecyclinebased combination therapy (multiple agents), there was no difference in clinical success, mortality, or microbiological outcomes [64,65]. Similarly, when evaluating tigecycline-based combination therapy versus non-tigecycline-based combination therapy, clinical cure and mortality outcomes were similar [66][67][68][69], while microbiological eradication with tigecyclinebased therapy was significantly lower in one trial [67]. In a more recent evaluation of 238 adult ICU patients with CRAB pneumonia, those treated with tigecycline-based combination therapies had higher ICU mortality than non-tigecycline therapy (adjusted odds ratio 2.30, 95% confidence interval 1.19-4.46) [70].…”
Section: Combination Therapiesmentioning
confidence: 98%
“…Indeed, it is certainly relevant to have the same fears with respect to antifungals use that with respect to antibiotics (27,28). Limiting wide use would limit the emergence of resistant strains (29).…”
Section: Editorialmentioning
confidence: 99%